(untitled) (Bangladesh Journal of Medical Science, 2014)
Osteoma is the most frequent benign tumor of paranasal sinuses. Usually osteomas are asymptomatic and discovered incidentally during radiological imaging for other reasons. A giant osteoma with intraorbital extension is rare. Plain radiograph may be useful; however CT scan is the best modality of investigation for diagnosing and treatment planning. In asymptomatic osteomas, serial follow-up can be done. Surgery is performed in the presence of symptoms and signs. We report a case of 60 years old woman with a large osteoma of right ethmoid sinus extending into the ipsilateral orbital cavity. DOI: http://dx.doi.org/10.3329/bjms.v14i1.20925 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.95-97